2000
DOI: 10.1590/s0103-90162000000300010
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de nutrientes por células de algodoeiro cultivadas em suspensão

Abstract: *Autor correspondente RESUMO: Com o objetivo de conhecer os requerimentos nutricionais de suspensões celulares de algodoeiro foi feita uma análise da utilização de nutrientes no intervalo de 30 dias, normalmente utilizado entre subculturas. As culturas de células em suspensão de algodoeiro, genótipo 101-102B, foram estabelecidas e subcultivadas mensalmente em meio líquido. Foram analisadas o crescimento das culturas, as variações de pH do meio de cultura e a absorção de nutrientes. A matéri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…This phase was of short duration probably because the suspensions were already th with 10 months of culture when the growth curve began. A lag phase of short Celedón et al [21]. The authors reported that although the curve obtained is similar to the curve model in suspensions of plant cells, the lag existent.…”
Section: Transmission Electron Micrography Of Cell Suspensions Of Coffea Arabica In Reference To the 4 Th (A And B) And 28 Th Day (C And mentioning
confidence: 79%
“…This phase was of short duration probably because the suspensions were already th with 10 months of culture when the growth curve began. A lag phase of short Celedón et al [21]. The authors reported that although the curve obtained is similar to the curve model in suspensions of plant cells, the lag existent.…”
Section: Transmission Electron Micrography Of Cell Suspensions Of Coffea Arabica In Reference To the 4 Th (A And B) And 28 Th Day (C And mentioning
confidence: 79%